“Inevitable” and “Imminent” Invasions: The Logic Behind Western Media War Stories - G. Simons (Международная аналитика, 2022)
In the 21st century, great power geopolitics is back as the Western-centric U.S. unipolar order is facing relative decline due to the challenges posed by the non-Western-centric multipolar order, specifi cally by China and Russia. In political and practical terms, geopolitics is about being able to manage and represent the nature of international relations in terms of actor relations and power dynamics. It concerns the ability of actors to make representations and interpretations of actors, events, and processes taking place in the physical realm. Informational geopolitics as an indirect and non-kinetic form of competition and confl ict has gained increasing prominence in the 21st century, where information and knowledge form the fi fth dimension of strategy. This leads to increasingly unstable international relations as the U.S. seeks to prevent other powers from growing at its expense. Hence, the critical role played by Western mainstream mass media outlets as a means of obstructive foreign policy in preserving the unipolar order through specifi c discursive practices employed in international news. Critical discourse analysis is used to analyse and interpret Western news stories on “inevitable” and “imminent” Chinese and Russian invasions. Informational geopolitics is used as a means of limiting opponent’s operational choices and opportunities in their pursuit of foreign policy objectives.